PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PABRIK PADA PT. INTI KARYA PLASMA PERKASA TAPUNG - Kholil, Muhammad Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted at Factory PT. Inti Karya Plasma Perkasa Tapung the aim to determine the effect of variables discipline on the performance of the employees, work environment on employees performance and both variables discipline and work environme simultaneously affect employee the performance factory at PT.Inti Karya Plasma Perkasa Tapung. The technique used in this study is the technique Slovin (Umar, 2008: 82) to obtain a sample amounted to 107 employees of population 139 employees. The analysis of the data used is analysis descriptive, as it also uses analysis quantitative ie using regression multiple linear with SPSS version 20. From the results of testing that has been done, the regression test (Test-F) shows that discipline and work environment simultaneously affect on employee performance. Results (t-test) showed that the variables discipline affect the performance of the employees and work environment affect the performance of employees. Based on research, the company must improve discipline employees in the work and pay attention to the condition of the environment in which the employee works for the performance of the resulting line with company objectives.Keywords: Performance, discipline and work environme